FEMALE RIVALRY IN ELENA FERRANTE’S MY BRILLIANT FRIEND: A SOCIOLOGICAL APPROACH - Lestari, Novi Dwi; Pratiwy, Devi (JOURNAL OF LANGUAGE, 2025)
This study analyzes the phenomenon of female rivalry in Elena Ferrante’s My Brilliant Friend, focusing on the complex relationship between the two protagonists, Elena “Lenu” Greco and Raffaella “Lila” Cerullo. Employing a qualitative descriptive method and the sociology of literature approach, the research explores both the contents and underlying factors of their rivalry. Data were collected through close reading and analyzed based on theoretical frameworks concerning female competition. The findings reveal that the rivalry between Lenu and Lila centers on three main dimensions: attractiveness, encompassing Lila’s intellectual brilliance and magnetic personality; beauty and physical appearance, which create deep insecurities for Lenu; and similarity of interests, particularly their shared passion for learning and recognition. These dynamics are further intensified by two driving factors: competition for male attention and Lenu’s persistent lack of self-confidence. The study concludes that female rivalry, even within a deep friendship, functions as both a source of motivation and emotional struggle, reflecting broader societal expectations surrounding women’s beauty, intellect, and desirability.